A new bent-toed gecko (Squamata: Gekkonidae: Cyrtodactylus) from the Kimberley region, Western Australia - Bauer, Aaron M.; Doughty, Paul (Zootaxa, 2012)
A diminutive new species of Cyrtodactylus is described from East Montalivet Island off the north coast of the Kimberley regionof Western Australia. Cyrtodactylus kimberleyensis sp. nov. may be distinguished from all other congeners by its small size(gravid female holotype 45 mm SVL), its lack of enlarged subcaudal plates, 16–18 rows of dorsal tubercles, weakly developedventrolateral skin fold, and dorsal pattern lacking dark transverse bands and enlarged blotches. The new species is one of thesmallest in the genus and is the first Cyrtodactylus known from Western Australia. It is not closely related to the large-bodiedspecies of the Cape York Peninsula, Queensland, but rather has affinities to small to mid-sized species occurring on Timor and in the Lesser Sundas, and thus represents a second pathway of colonization of northern Australia.